2014
DOI: 10.1001/jamaoto.2014.821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p16 and Its Relationship With Human Papillomavirus in Pharyngeal Squamous Cell Carcinomas

Abstract: p16 Was not associated with improved outcomes in patients with HP or NP SCC. The positive predictive value of p16 as a test for HPV is too low for p16 testing alone in the HP and NP. However, p16 negativity is sufficient to rule out HPV. As a research approach, we recommend p16 immunohistochemistry as a screening test for HPV in NP SCC and HP SCC followed by confirmatory HPV in situ hybridization when p16 positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…However, the significance of p16 expression and its relationship with HPV is also unclear for SCC, as well as for urothelial carcinoma in situ, and the correlation between p16 expression and rat sarcoma/mitogen-activated protein kinase pathway should also be better studied for these neoplasms. 10 In conclusion, the present case is interesting because it confirms the potential role of HPV in bladder carcinogenesis, and shows the association between HPV genital tract infection, repeated catheterizations and BSCC of the bladder. It suggests that BSCC of the bladder is strictly related to HPV infection, and Human papillomavirus type 16 Good Score: 100…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, the significance of p16 expression and its relationship with HPV is also unclear for SCC, as well as for urothelial carcinoma in situ, and the correlation between p16 expression and rat sarcoma/mitogen-activated protein kinase pathway should also be better studied for these neoplasms. 10 In conclusion, the present case is interesting because it confirms the potential role of HPV in bladder carcinogenesis, and shows the association between HPV genital tract infection, repeated catheterizations and BSCC of the bladder. It suggests that BSCC of the bladder is strictly related to HPV infection, and Human papillomavirus type 16 Good Score: 100…”
Section: Discussionsupporting
confidence: 72%
“…These findings and the detection of HPV DNA in the bladder neoplastic tissue suggest that, in our case, the overexpression of p16 in the neoplastic cells was not as a result of the rat sarcoma/mitogen‐activated protein kinase pathway, and that it was related to HPV. However, the significance of p16 expression and its relationship with HPV is also unclear for SCC, as well as for urothelial carcinoma in situ , and the correlation between p16 expression and rat sarcoma/mitogen‐activated protein kinase pathway should also be better studied for these neoplasms . In conclusion, the present case is interesting because it confirms the potential role of HPV in bladder carcinogenesis, and shows the association between HPV genital tract infection, repeated catheterizations and BSCC of the bladder.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, these results raise the question of whether it is worth routinely evaluating HPV in patients with NPC, an issue that has not been addressed heretofore by national recommendations. 33 Moreover, Wilson and colleagues 11 suggested that p16 testing had a positive predictive value of just 67% in NPC, albeit with just 13 NPC cases, but other methods may improve detectability. 37 Nevertheless, although we are limited in that the NCDB does not describe the method of HPV evaluation, our data do not support a role for routine HPV testing in NPC for prognostic or management purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as a result of small-volume reports, there are conflicting data as to whether or not HPV is associated with an improved prognosis in NPC. [9][10][11][12][13][14][15] Indeed, as the focus of HPV-induced OPC enters the realm of phase III trials that could change clinical management, it is becoming increasingly critical to address with largevolume investigations whether there are links between HPV and prognoses in other head and neck neoplasms.…”
mentioning
confidence: 99%
“…The latter is primarily associated with heavy tobacco and alcohol exposure. HPV status in non-oropharyngeal HNSCC, including cancers of the oral cavity, hypopharynx and larynx, has not been clearly associated with a similar improved prognosis, suggesting that either HPV may not be playing a major role in pathogenesis of HNSCC outside of the oropharynx or that other features are more important for prognosis at these anatomic sites (7275). Given the relation to prognosis it is essential to correctly identify HPV-positive cases.…”
Section: Clinical Perspectivesmentioning
confidence: 99%